Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1097/ta.0000000000003562
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous lidocaine for the management of traumatic rib fractures: A double-blind randomized controlled trial (INITIATE program of research)

Abstract: Lidocaine a success for analgesia treating pain from traumatic rib fractures, particularly during mobilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In a recent randomized controlled study, 36 patients were randomized to IVL or placebo. Although pain scores, patient satisfaction, and opioid consumption were lower in the lidocaine group, the study was not powered for statistical significance 41 . Similarly, a retrospective review of 414 patients showed decreased opioid consumption, lower pain scores, and reduced hospital costs with IVL in rib fractures compared with patients without IVL 42 .…”
Section: Regional Anesthesia For Rib Fracturesmentioning
confidence: 95%
See 1 more Smart Citation
“…In a recent randomized controlled study, 36 patients were randomized to IVL or placebo. Although pain scores, patient satisfaction, and opioid consumption were lower in the lidocaine group, the study was not powered for statistical significance 41 . Similarly, a retrospective review of 414 patients showed decreased opioid consumption, lower pain scores, and reduced hospital costs with IVL in rib fractures compared with patients without IVL 42 .…”
Section: Regional Anesthesia For Rib Fracturesmentioning
confidence: 95%
“…Although pain scores, patient satisfaction, and opioid consumption were lower in the lidocaine group, the study was not powered for statistical significance. 41 Similarly, a retrospective review of 414 patients showed decreased opioid consumption, lower pain scores, and reduced hospital costs with IVL in rib fractures compared with patients without IVL. 42 When compared with TEA in a retrospective study of 89 patients, IVL resulted in similar pain scores and a potential opioid-sparing effect secondary to increased total MME in the TEA group when accounting for neuraxial opioids in that group.…”
Section: Intravenous Lidocainementioning
confidence: 96%
“…We would like to thank Drs. Kasetti and Sonawane for providing thoughtful feedback on our published study, “Intravenous lidocaine for the management of traumatic rib fractures: A double-blind randomized controlled trial,” and appreciate the opportunity to respond to their recommendations 1 …”
mentioning
confidence: 99%
“…Kasetti and Sonawane for providing thoughtful feedback on our published study, "Intravenous lidocaine for the management of traumatic rib fractures: A double-blind randomized controlled trial," and appreciate the opportunity to respond to their recommendations. 1 Drs. Kasetti and Sonawane cite concern about the lack of a clear definition of movement and mention that "pain with touch, taking a deep breath, sneezing, and coughing" are common activities that cause pain in patients with rib fractures.…”
mentioning
confidence: 99%
“…We read with great interest the article “Intravenous lidocaine for the management of traumatic rib fractures: A double-blind randomized controlled trial (INITIATE program of research)” by Patton et al, 1 where intravenous lidocaine was proposed to be an effective analgesic in the management of traumatic rib fractures (TRFs). The authors compared lidocaine with placebo infusion in adults with two or more TRFs and found a pain reduction with movement in patients with lidocaine compared with placebo.…”
mentioning
confidence: 99%